2017
DOI: 10.1093/ons/opx071
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Complications Following Acoustic Neuroma Resection

Abstract: We present lower rates of ophthalmic complications following ANR than previously reported. Improved surgical technique, better postoperative eye care, and facial nerve monitoring most likely accounted for the improved ocular outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…However, the direct impact of VII nerve monitoring on post-operative VII function is yet to be elucidated. 16 , 27 Stereotactic radiosurgery has lower rates of post-treatment VII nerve weakness with less than 1% of patients in our own neurosurgical unit having persistent VII nerve weakness following Gamma knife radiosurgery. 29 Whilst traditionally reserved for smaller tumor sizes, stereotactic radiosurgery can achieve reasonable tumor control even for larger volume VSs of greater than 10cm 3 .…”
Section: Facial (Vii) Nerve Weaknessmentioning
confidence: 91%
See 4 more Smart Citations
“…However, the direct impact of VII nerve monitoring on post-operative VII function is yet to be elucidated. 16 , 27 Stereotactic radiosurgery has lower rates of post-treatment VII nerve weakness with less than 1% of patients in our own neurosurgical unit having persistent VII nerve weakness following Gamma knife radiosurgery. 29 Whilst traditionally reserved for smaller tumor sizes, stereotactic radiosurgery can achieve reasonable tumor control even for larger volume VSs of greater than 10cm 3 .…”
Section: Facial (Vii) Nerve Weaknessmentioning
confidence: 91%
“… 78 One series reported two cases (1.1%) of peri-orbital cellulitis following VS resection. 16 Finally, Roland et al reported one case of a persistent Horner’s syndrome following resection of a VS. 54 This was, however, associated with a severe sialadenitis (salivary gland inflammation) and a large neck phlegmon, which also caused a temporary palsy of the lower cranial nerves and the brachial plexus.…”
Section: Miscellaneousmentioning
confidence: 99%
See 3 more Smart Citations